2018
DOI: 10.1037/lhb0000268
|View full text |Cite
|
Sign up to set email alerts
|

Associations between posttraumatic stress and legal charges among substance using veterans.

Abstract: Substance misuse is prevalent among veterans entering the criminal justice system, and is related to recidivism. Research demonstrates that trauma exposure and posttraumatic stress (PTS) symptoms, which commonly co-occur with substance misuse, also increase the risk of legal involvement and recidivism. However, it is unclear whether the associations between trauma, PTS symptoms and violent and nonviolent crime may be conflated by substance use. The aim of the present study was to understand the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 79 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…Several articles focused on conditions and experiences related to military service such as PTSD and trauma (Backhaus et al, 2016; Bennett, Morris, Sexton, Bonar, & Chermack, 2018; Elbogen et al, 2012; Saxon et al, 2001; Sigafoos, 1994). A number of observational studies addressed violence (Elbogen et al, 2012; Hoyt et al, 2014; MacManus et al, 2013) and Veterans Treatment Courts (Clark, Blue-Howells, & McGuire, 2014; Knudsen & Wingenfeld, 2016; Tsai, Flatley, Kasprow, Clark, & Finlay, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several articles focused on conditions and experiences related to military service such as PTSD and trauma (Backhaus et al, 2016; Bennett, Morris, Sexton, Bonar, & Chermack, 2018; Elbogen et al, 2012; Saxon et al, 2001; Sigafoos, 1994). A number of observational studies addressed violence (Elbogen et al, 2012; Hoyt et al, 2014; MacManus et al, 2013) and Veterans Treatment Courts (Clark, Blue-Howells, & McGuire, 2014; Knudsen & Wingenfeld, 2016; Tsai, Flatley, Kasprow, Clark, & Finlay, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Court mandates for treatment were not recorded in these databases. Single VHA site studies used criminal justice data gathered through randomized controlled trials (Anderson et al, 2017; Bennett et al, 2018), longitudinal treatment surveys (Atkinson, Tolson, & Turner, 1993; Timko et al, 2017), and one-time questionnaires (Backhaus et al, 2016; Briggs et al, 2001). Multiple VHA site studies included qualitative interviews (Blonigen et al, 2018), longitudinal assessments (Tsai, Middleton, et al, 2017), and administrative evaluation data (Coker & Rosenheck, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark et al (2014) reported that regular substance users with a history of trauma were more likely to report histories of violent offending than individuals with either substance use problems or trauma histories alone. Bennett et al (2018) found that within a large sample (n = 697) of trauma-exposed veterans in SUD clinics, violent legal charges were associated with greater posttraumatic stress symptom severity. In an Australian sample of 102 men and women seeking outpatient services for comorbid PTSD and SUD, higher levels of aggression and PTSD hyperarousal symptoms were found to predict past-month violent criminality (Barrett et al, 2011).…”
mentioning
confidence: 90%
“…The PTSD symptom cluster of hyperarousal, in particular, has been linked to aggression in veterans (Taft et al, 2007), a nationallyrepresentative sample of non-institutionalized adults (Smith, Smith, Violanti, Bartone, & Homish, 2015), as well as civilians with comorbid PTSD+SUD (Barrett, Mills, & Teesson, 2011;Barrett, Teesson, & Mills, 2014). However, recent work with substance-using veterans identified the intrusion symptom cluster as uniquely predictive of violent criminality (Bennett, Morris, Sexton, Bonar, & Chermack, 2018).…”
mentioning
confidence: 99%